Glucose Homeostasis during the Perioperative Period of Cardiac Surgery: A Narrative Review - Redant, Sébastien; Bels, David De; Villet, Benoit; Attou, Rachid; Honore, Patrick M; Schmartz, Denis; Carbognani, Daniel (Cardiology and Cardiovascular Medicine, 2021)
Hyperglycemia and insulin resistance are frequent in intensive care patients and have been associated with worse outcomes. The control of blood glucose levels has an impact on the morbidity and mortality of intensive care patients. The authors focused on the perioperative period of cardiac surgery and reviewed the various mechanisms that contribute to hyperglycemia, such as surgical trauma, heparinization, cooling, rewarming and cardioplegia. The consequences of perioperative hyperglycemia in terms of morbidity and mortality, and the possible management strategies (including GIK, GIN and normoglycemic hyperinsulinism) were also reviewed.